2010
DOI: 10.1073/pnas.1011418108
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis signal-regulating kinase 1 and cyclin D1 compose a positive feedback loop contributing to tumor growth in gastric cancer

Abstract: Mitogen-activated protein kinase (MAPK) pathways regulate multiple cellular functions and are highly active in many types of human cancers. Apoptosis signal-regulating kinase 1 (ASK1) is an upstream MAPK involved in apoptosis, inflammation, and carcinogenesis. This study investigated the role of ASK1 in the development of gastric cancer. In human gastric cancer specimens, we observed increased ASK1 expression, compared to nontumor epithelium. Using a chemically induced murine gastric tumorigenesis model, we ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
93
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 94 publications
(99 citation statements)
references
References 59 publications
3
93
0
Order By: Relevance
“…27,30 Many studies have reported differential regulation of cyclin D1 and its effects on the proliferative state of diseased cells. [31][32][33] Mutations in the 3' UTR of cyclin D1 are also responsible for the hyperproliferative state associated with a variety of tumors types. 34 Cells expressing a cyclin D1 that lacks a 3' UTR also show a higher rate of proliferation.…”
Section: Kip1mentioning
confidence: 99%
“…27,30 Many studies have reported differential regulation of cyclin D1 and its effects on the proliferative state of diseased cells. [31][32][33] Mutations in the 3' UTR of cyclin D1 are also responsible for the hyperproliferative state associated with a variety of tumors types. 34 Cells expressing a cyclin D1 that lacks a 3' UTR also show a higher rate of proliferation.…”
Section: Kip1mentioning
confidence: 99%
“…In addition, ASK1 plays pivotal roles in a wide variety of cellular responses, which include, but are not limited to, apoptosis (30,31). Dysregulation of the ASK1 signaling pathway is closely linked to various diseases, such as cancer, cardiovascular diseases, diabetes, and neurodegenerative diseases including polyglutamine-induced neurodegeneration and Parkinson disease (29,(32)(33)(34)(35)(36)(37).…”
mentioning
confidence: 99%
“…The key initiator role of ASK1-3 in this pathway means that either too much or too little ASK activity can have pathological effects. For instance, inhibiting ASK1 is beneficial against gastric cancer (13,14), but inactivating mutations in ASK1 contribute to the development of melanoma (15, 16). In addition, ASK1 inhibitors have shown promise for treatment in mouse models of amyotrophic lateral sclerosis, highlighting it as a critical factor modulating cellular survival (17).…”
mentioning
confidence: 99%